Factors contribute to the risk in field activities towards general workers in oil palm plantation / Muhamad Aqil Rosman - Rosman, Muhamad Aqil (Faculty of Plantation and Agrotechnology, 2018)
Safety is the most aspects of any activity or work which need to implemented by organization at the workplace in various types of industries. There was no exception for agriculture industry which most of the workers is human being especially in plantation industry. This is because, the workers are exposed to several of the hazard that need to face in the plantation including fall and slip, chemical spillage, heat stress, accidently step on sharp objects, and venomous attacked. Therefore, this study was conducted to know the factor that can contributes to the risk in field activities towards general workers in oil palm plantation. This study also conducted to determine the relationship between the factors with rate of accidents and health among the workers. There are four factors that were studied such as personal protective equipment (PPE), skilled and unskilled workers, training and management. The data was collected by distributing the questionnaire at Ladang Risda Bera which the total respondent is 67 general workers that including harvesting, manuring, spraying herbicides, and the driver. The result shows that, training is the most factors that can contribute to the high rate of accidents in oil palm plantation among the other factors that has been studied. Through correlation analysis shows that there is relationship between all the factors with rate of accidents towards general workers in field activities in plantation.